Effects of estrogen and mechanical loading on cultured cells derived from mandibular condylar cartilage - Jin Tsuchida; Yuya Nakao; Koken Sato; Osamu Uehara; Itaru Mizoguchi; Yoshihiro Abiko; Masahiro Iijima (Scientific Reports)
Abstract Temporomandibular joint osteoarthritis (TMJ-OA) is a degenerative condition influenced by mechanical loading and hormonal factors, particularly estrogen. Despite its established role in TMJ pathophysiology, the mechanisms underlying the effects of estrogen on joint cartilage remain unclear, with conflicting reports regarding its protective and destructive effects. This study aimed to investigate the molecular effects of estrogen and mechanical loading on cultured cells derived from mandibular condylar cartilage (MCC). The chondrogenic identity of cells was confirmed using quantitative reverse transcription PCR (qRT-PCR). The cells were then subjected to mechanical loading with or without 17β-estradiol treatment. RNA sequencing and bioinformatics analyses, including differential gene expression, Gene Ontology, and protein–protein interaction network analysis, identified extracellular matrix (ECM)-related pathways and hub genes, such as COL1A1, COL3A1, LAMC1, and LAMB1, as key mediators. Mechanical loading reduced the expression of ECM-related genes in MCC cells, whereas estrogen combined with loading significantly upregulated COL1A1 and COL3A1 expression, as confirmed by qRT-PCR and western blotting. This study demonstrated the effects of estrogen on mechanical loading using superficial condylar cells to elucidate the mechanisms of TMJ. Estrogen may be, at least in part, significantly involved in TMJ-OA via altering of the ECM levels such as collagen, laminin, MMPs, and ADAMTS.